IMPLEMENTATION OF TRADITIONAL BATAKNESE ETHNIC ORNAMENTS IN CERAMIC CRAFT - Wahyu Tri Atmojo (International Conference on Languages and Arts, 2014)
This paper is part of Competitive Grant second year (2014) research titled ―The Creation of Ceramic Craft Based on Bataknese Ethnic Art as a Local Specialty with Global Nuance‖. This research aims to produce ceramic works of art by implementing traditional ornaments of Bataknese ethnic of North Sumatra. In the first year (2013), 30 ceramic craft‘s structural designs and Bataknese ethnic ornament design sketches have been produced. This study is a new formula related to Ceramic Craft Based on Bataknese Ethnic Art as a Local Specialty with Global Nuance. In the second year (2014), the traditional Bataknese ethnic ornamental designs are implemented to the ceramic craft‘s structure. The application of the ornamental design is done in three stages. The first stage is to apply the design to ceramic structures using a pencil. The second stage is to color the design with Bataknese ethnic colors of red, black, and white by using poster and wall paint. The third stage is to provide a layer of clear-lacquer-colored acrylic so that the color from poster and wall paper is not scratched. Thus, in this second year, ceramic craft which have been decorated with Bataknese ethnic of North Sumatra ornamental motifs have been produced. Since this Competitive Grant study lasts for 3 (three) years, the plan in the third year (2015) is to conduct a ceramic crafts exhibition, to do focus group discussion (FGD) involving artisans, faculty and students of the Fine Arts Department of the Faculty of Languages and Arts, State University of Medan, arts practitioners, and the media.